PENERAPAN CRITICAL REVIEW ARTIKEL PEMBELAJARAN IPA UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA DALAM MENYUSUN PROPOSAL SKRIPSI - parmin, p (Sains and Technology Faculty, Walisongo State Islamic University, 2014)
The aims of this research is to improve studentsâ ability in develop- ing a proposal thesis by applying critical review of scientific articles come from journals. The research is designed by class action research. The results showed 63% of students thesis proposals on Research Methodology course scored above 80. Based on the results obtained it can be concluded that the application has been critical review or critical study of scientific articles can enhance studentsâ ability in preparing research proposals.